Green biosynthesis of silver nanoparticles using Callicarpa maingayi stem bark extraction - Shameli, Kamyar; Ahmad @ Ayob, Mansor; Al-Mulla, Emad A. Jaffar; Ibrahim, Nor Azowa; Shabanzadeh, Parvaneh; Rustaiyan, Abdolhossein; Abdollahi, Yadollah; Bagheri, Samira; Abdolmohammadi, Sanaz; Usman, Muhammad Sani; Zidan, Mohammed (MDPI, 2012)
Different biological methods are gaining recognition for the production of silver nanoparticles (Ag-NPs) due to their multiple applications. The use of plants in the green synthesis of nanoparticles emerges as a cost effective and eco-friendly approach. In this study the green biosynthesis of silver nanoparticles using Callicarpa maingayi stem bark extract has been reported. Characterizations of nanoparticles were done using different methods, which include; ultraviolet-visible spectroscopy (UV-Vis), powder X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy dispersive X-ray fluorescence (EDXF) spectrometry, zeta potential measurements and Fourier transform infrared (FT-IR) spectroscopy. UV-visible spectrum of the aqueous medium containing silver nanoparticles showed absorption peak at around 456 nm. The TEM study showed that mean diameter and standard deviation for the formation of silver nanoparticles were 12.40 ± 3.27 nm. The XRD study showed that the particles are crystalline in nature, with a face centered cubic (fcc) structure. The most needed outcome of this work will be the development of value added products from Callicarpa maingayi for biomedical and nanotechnology based industries.